Penentuan Lokasi SMP Baru di Kabupaten Klungkung dengan Algoritma Fuzzy Subtractive Clustering - Artawan, I Gede Oka; Gandhiadi, G. K.; Oka, Tjokorda Bagus (Jurnal Matematika, 2022)
The aim of this paper is to determine a new location of junior high school at Klungkung, using Fuzzy Subtractive Clustering Algorithm. The new location of the junior high school is depending on the graduate number of elementary school, the distance between location of candidates, and distance between the candidates’ location and existing junior high school. To measure the distance, it is used an Euclidean distance. At the beginning of calculation, the locations of elementary schools are used as the location candidates. Then, the density value of each location candidates is calculated using Fuzzy Subtractive Clustering Algorithm. The location candidate which has the highest density will be chosen to become a starting location. The results of calculation show that the location candidate at 8°32'5.70"S, 115°24'20.64"E has the highest density value, it is at SD Negeri 1 Semarapura Kangin. So the location for the new junior high school is at around SD Negeri 1 Semarapura Kangin.
Keywords: Density Value; Euclidean Distance; Fuzzy Subtractive Clustering Algorithm; Location of New Junior High School